Analysis of the PPARD gene expression level changes in football players in response to the training cycle - Domańska-Senderowska D; Snochowska A; Szmigielska P; Jastrzębski Z; Jegier A; Kiszałkiewicz J; Dróbka K; Jastrzębska J; Pastuszak-Lewandoska D; Cięszczyk P; Maciejewska-Skrendo A; Zmijewski P; et al. (Balkan Journal of Medical Genetics, 2018)
The PPARD gene codes protein that belongs to the peroxisome proliferator-activated receptor (PPAR) family engaged in a variety of biological processes, including lipid metabolism in muscle cells. In this study, we assess the relationship between PPARD gene expression lipid metabolism parameters and the variation of the PPARD gene expression before (T1) and after 12 hours of training (T2) sessions in a group of football players. Peripheral blood lymphocytes were obtained from 22 football players (17.5±0.7 years, 178±0.7 cm, 68.05±9.18 kg). The PPARD gene expression, analyzed by quantitative polymerase chain reaction (qPCR), was significantly higher after T2 (p = 0.0006). Moreover, at the end of the training cycle, there was a significant decrease in relative fat tissue (FAT) (%) (p = 0.01) and absolute FAT (kg) (p = 0.01). A negative correlation was observed between absolute FAT (kg) and PPARD gene expression level in T2 (p = 0.03). The levels of cholesterol and triglyceride (TG) fractions were not significantly different (p >0.05) before and after training. No significant relationship between PPARD expression and cholesterol or TG levels was found. We found that physical training affects PPARD expression. Moreover, the negative correlation between PPARD expression and absolute FAT (kg) level may be indicative of the contribution of PPARD in metabolic adaptation to increased lipid uptake that can be used to control the body composition of athletes.